Aktivitas Antibakteri Ekstrak Etanol Daun Ketapang (Terminalia catappa L.) Merah dan Cokelat Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Luh Made Ary Somia Vagestini; Retno Kawuri; Made Ria Defiani (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2023)
Staphylococcus aureus is known as bacteria that often cause respiratory tract disease in Indonesia. These bacteria are known to have developed resistance to several antibiotics. This study aims to analyze the comparison of the antibacterial activity of ethanol extracts of red ketapang leaves and brown ketapang leaves on the growth of S.aureus bacteria, determine the MIC of the two extracts, and determine the class of compounds in the extracts. The research method used includes sample extraction using the maceration method with 96% ethanol as solvent. The antibacterial activity test of the extract was carried out at concentrations of 20%, 15%, 10%, and 5% (w/v) with the disc diffusion method on Nutrient Agar media, and qualitative phytochemical tests were carried out. The results showed that the difference in leaf color affected the inhibition of S. aureus bacteria. The best inhibition was obtained at a concentration of 20% (w/v) red ketapang extract with an inhibition zone diameter of 13.67±0.76 mm. The results of the MIC test showed that the MIC value of the red ketapang extract was obtained at a concentration of 5% (w/v) with an inhibitory power of 1.47±0.25 mm and the cocoa bean leaf extract was obtained at a concentration of 10% (w/v) with the diameter of the inhibition zone. 1.73±0.25mm. The phytochemical test of the extracts showed that both extracts contained alkaloids, saponins, flavonoids, tannins, and steroids, but terpenoid compounds were only found in the red ketapang leaf extract. Keywords: secondary metabolites, MIC, resistance, ketapang leaf color.